Stereocontrol Strategies in the Asymmetric Bioreduction of Alkenes - Oberdorfer, Gustav; Gruber, Karl; Faber, Kurt; Hall, Mélanie (Synlett, 2012)
The asymmetric bioreduction of prochiral conjugated alkenes using ene-reductases allows powerful strategies to access both enantiomers of the product with high stereoselectivity. This may be achieved (i) by using pairs of (iso)enzymes, which bind the alkene moiety in mirror-image orientations to affect hydride attack from opposite sides, (ii) via a switch in the (E/Z)-geometry of the alkene unit, or (iii) by changing the size of the protective groups of the substrate, which enforces a flipped orientation in the active site. Modeling studies provide a rationale for the molecular basis of substrate binding and allow the prediction of the stereochemical outcome of this useful bioreduction. 1 Introduction2 Enzyme-Based Stereocontrol: ‘Enantiomeric’ Ene-reductases3 Substrate-Based Stereocontrol: Flipping Substrates3.1 Stereocontrol via (E/Z)-Configuration of Substrate3.2 Stereocontrol via Substituent Effects4 Modeling of Substrate Complexes5 Conclusions
Keywords: biocatalysis; stereocontrol; ene-reductase; asymmetric alkene reduction; Old Yellow Enzyme